2021
DOI: 10.1152/physrev.00021.2020
|View full text |Cite
|
Sign up to set email alerts
|

G protein-coupled receptor-G protein interactions: a single-molecule perspective

Abstract: G protein-coupled receptors (GPCRs) regulate many cellular and physiological processes, responding to a diverse range of extracellular stimuli including hormones, neurotransmitters, odorants and light. Decades of biochemical and pharmacological studies have provided fundamental insights into the mechanisms of GPCR signaling. Thanks to recent advances in structural biology, we now possess an atomistic understanding of receptor activation and G protein coupling. However, how GPCRs and G proteins interact in livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 481 publications
1
60
0
Order By: Relevance
“…S3-S4). These data are highly relevant to our mechanistic understanding of the signal propagation through GPCR/G protein pathways (23). The two predominant models of G protein activation are collisional coupling (26-28) and pre-assembled complexes (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S3-S4). These data are highly relevant to our mechanistic understanding of the signal propagation through GPCR/G protein pathways (23). The two predominant models of G protein activation are collisional coupling (26-28) and pre-assembled complexes (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Canonically, GPCRs catalyze the dissociation of Gαβγ into active Gα and Gβγ signaling units that can participate in downstream signaling events. The interactions between GPCRs and G proteins have been probed extensively using several fluorescencebased techniques including resonance energy transfer, bimolecular complementation, single molecule tracking, polarization, and FFS (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…It is still conceivable that GRK5 and 6 interactions with certain GPCRs might be obstructed due to their distinct cellular localisation. The plasma membrane features a rather heterogeneous distribution of proteins and it has been shown that certain GPCRs tend to reside in specific membrane confinements 56 . Some receptors might localise in membranous compartments that are inaccessible for GRK5 and 6.…”
Section: Discussionmentioning
confidence: 99%
“…Although we are unable to exclude the possibility that AWC-sensed chemicals share a broadly tuned receptor that alters neuronal responses based on odorant context (MacWilliam et al, 2018;Turner and Ray, 2009), we favor the notion that saturation with an AWC-sensed chemical (and/or mutations in odr-1) alters neuronal state in a manner that then dictates the differential usage of intracellular signaling pathways by medium-chain alcohol receptor(s) to elicit distinct sensory responses. The as yet unidentified hexanol (and heptanol) receptor(s) may be modified in a neuronal state-dependent manner to promote coupling to distinct effector pathways upon ligand binding (Calebiro et al, 2021;Flock et al, 2017;Patwardhan et al, 2021). Alternatively, differential compartmentalization of signaling complexes within the AWC sensory cilia membrane may promote the usage of distinct signal transduction machinery in different neuronal conditions (Ellisdon and Halls, 2016;Hilgendorf et al, 2019;L'Etoile and Bargmann, 2000;Langeberg and Scott, 2015;Polit et al, 2020).…”
Section: Discussionmentioning
confidence: 99%